The Relationship Between Knowledge Level and Efforts TO Reduce Blood Pressure in Patients with Hypertension in Tanara Village in 2022 - Monika, Viki Indah; Vanchapo, Antonius Rino; Jayadi, Alpian; Tusi, Juandri Seprianto; Lewar, Emanuel Suban Bala; Barroso, Uwe; Intes, Amina (Journal of World Future Medicine, Health and Nursing, 2023)
Hypertension is called the silent killer disease because it often occurs without complaints because it does not show symptoms. People with high blood pressure do not realize they have high blood pressure because they have no symptoms. Hypertension is also known as hypertension when the systolic blood pressure rises to 140 mmHg and the diastolic blood pressure increases by 90 mmHg. This disease can lead to complications and death if not treated immediately. Purpose: to determine the relationship between the level of knowledge and efforts to reduce blood pressure in patients with hypertension. Methods: using descriptive correlation with cross sectional design with total sampling technique with a total sample of 36 people. Results. Data collection using 2 questionnaires. The results of the analysis using the Spearman rank correlation test (rho) obtained the results of p = 0.000 which means p (<0.05) this shows that there is a relationship between the level of knowledge and efforts to reduce blood pressure in patients with hypertension in the work area  of the  village  of  Tanara  in 2022.